Nuclear export of replication protein A in the nonreplicative infective forms of Trypanosoma cruzi - Pavani, Raphael S.; de Lima, Loyze P.; Lima, André A.; Fernandes, Carlos A. H. [UNESP]; Fragoso, Stenio P.; Calderano, Simone G.; Elias, Maria Carolina (Wiley, 2020)
Replication protein A (RPA), a heterotrimeric complex, is the major single-stranded DNA binding protein in eukaryotes. Recently, we characterized RPA from Trypanosoma cruzi, showing that it is involved in DNA replication and DNA damage response in this organism. Better efficiency in differentiation from epimastigote to metacyclic trypomastigote forms was observed in TcRPA-2 subunit heterozygous knockout cells, suggesting that RPA is involved in this process. Here, we show that RPA cellular localization changes during the T. cruzi life cycle, with RPA being detected only in the cytoplasm of the metacyclic and bloodstream trypomastigotes. We also identify a nuclear export signal (NES) in the trypanosomatid RPA-2 subunit. Mutations in the negatively charged residues of RPA-2 NES impair the differentiation process, suggesting that RPA exportation affects parasite differentiation into infective forms.
Keywords: NES; nuclear exportation; replication protein A; RPA; Trypanosoma cruzi